Out-of plane bending stiffness along the major axis of profiled steel sheet dryboard composite floor panels - Wan Hamidon Wan Badaruzzaman,; Ehsan Ahmed,; Khalim Rashid, (1996)
This paper presents the experimental investigation of the out-of plane bending behaviour of newly developed composite floor panels namely Profiled Steel Sheet Dryboard (PSSDB) composite panels. Such panels are formed by attaching dryboards to a core of profiled steel sheeting using mechanical connectors. It is very light and therefore easily transportable and can be erected quickly by semi-skilled labour. A series of out-of plane bending tests to investigate the overall structural performance, and the influence of connector modulus and spacing on the performance of the PSSDB panels will be described. The suitability of the component materials for these panels is also investigated. It will be shown that connector modulus and spacing play major roles in influencing the stiffness of such composite panels. Suitable choice of connector and spacing is important in determining the stiffness of these panels. Partial interaction approach developed by the authors can safely be used to design composite PSSDB floor panels along the major axis of bending. This theoretical approach will be shown to be giving acceptable conservative stiffness values